2011
DOI: 10.1352/1944-7558-116.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Marital Satisfaction and Parenting Experiences of Mothers and Fathers of Adolescents and Adults With Autism

Abstract: The association of marital satisfaction with parenting burden and quality of the parent-child relationship was examined in 91 married mothers and fathers of co-residing adolescents and adults with autism spectrum disorders. Within-couple differences between mothers and fathers in how child characteristics related to these parenting experiences were also evaluated. Multilevel modeling was used to control for the dependency in couple data. Marital satisfaction was an important predictor of parenting experiences,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 57 publications
8
69
1
1
Order By: Relevance
“…Similarly, parent-reported severity of autism symptoms was not related to parental relationship status in the Freedman et al (2011) study of 913 children with an ASD. These findings are in line with the large body of research showing that parenting stress is more strongly associated with level of behavior problems than intellectual disability status or autism symptoms (e.g., Baker, Blacher, Crnic, & Edlebrock, 2002; Baker et al, 2003; Hartley, Barker, Seltzer, Floyd, & Greenberg, 2011). …”
Section: Why Some Marriages Fare Better Than Otherssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, parent-reported severity of autism symptoms was not related to parental relationship status in the Freedman et al (2011) study of 913 children with an ASD. These findings are in line with the large body of research showing that parenting stress is more strongly associated with level of behavior problems than intellectual disability status or autism symptoms (e.g., Baker, Blacher, Crnic, & Edlebrock, 2002; Baker et al, 2003; Hartley, Barker, Seltzer, Floyd, & Greenberg, 2011). …”
Section: Why Some Marriages Fare Better Than Otherssupporting
confidence: 89%
“…The few studies on this topic show that parents indicate a strong association between marital satisfaction and the experience of parenting burden or stress (Essex & Hong, 2005; Essex, 2002; Hartley et al, in press; Kersh, Hedvat, Hauser-Cram, & Warfield, 2006). For instance, in our examination of 91 married mothers and fathers of co-residing adolescents and adults with an ASD, parents with above-average marital satisfaction were less burdened by their son or daughter than were parents with below-average marital satisfaction, after controlling for the level of their son or daughter's behavior problems (Hartley et al, 2011). …”
Section: Broadening the Perspective On Marital Qualitymentioning
confidence: 99%
“…The authors found that marital satisfaction was an important predictor of parenting experiences, and mothers of children with autism showed close relationships with children more than fathers. These results were corroborated by a study by Hartley et al [46] They found that mothers felt a closer relationship to their children with autism, rather than with the fathers.…”
Section: Parent-child Relationshipsupporting
confidence: 76%
“…The increased chaos seen in families of children with ASD may also contribute to increased parental conflict and decreased marital satisfaction seen in these families (Brobst et al 2009;Gau et al 2011;Harper et al 2013;Hartley et al 2011). The presence of emotional strain and relationship difficulties likely make it more difficult for children with ASD to learn appropriate social behaviors, as more maladaptive interactions are modeled by caregivers who are frequently engaged in conflict.…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%